Fear of Acquaintance Versus Stranger Rape as a Master Status : Towards Refinement of the Shadow of Sexual Assault - Jordan, Carol E. (2006)
Using a sample of 1,010 women from a southeastern state university, we explore whether associations between fear of sexual assault and other crime-specific fears vary based on presumed victim-offender relationship. More specifically, we assess the extent to which fear of stranger- and acquaintance-perpetrated sexual assaults differ in the extent to which they are correlated with fear of other crime victimizations. Multivariate logistic regression analysis revealed that both fear of stranger-perpetrated sexual assault and fear of acquaintance- perpetrated sexual assault were positively associated with nearly all other crimespecific fears under examination. However, associations were particularly strong between fear of sexual assault by a stranger and fear of other stranger-perpetrated crimes. Findings have significant implications for how academic institutions should comprehensively address direct and indirect negative influences of violence against college women